THE TEACHER’S STRATEGIES IN TEACHING WRITING DESCRIPTIVE TEXT AT SENIOR HIGH SCHOOL - Fitri Febriyanti Lubis; Willem Saragih (Universitas Negeri Medan, 2022)
This study focuses on the analysis of teacher’s strategies of teaching writing descriptive text. The objectives of this study were (1) to describe the strategies used by the teacher inteaching writing descriptive text; (2) to know the reasons why the strategies used by the teacher in teaching writing descriptive text. This study was qualitatively conducted that involved one English teacher of SMA Swasta An-Nizam Medan. The data were collected by observing the teacher’s activities during teaching writing descriptive text. Then, the researcher interviewed the teacher about his reasons of the teacher's ways in teaching writing descriptive text. The findings of the study showed that the teacher’s strategies are similar with theory of the strategies by Judie Haynes and Debbie Zacarian such as (1) make visual lesson (2) determine key concepts (3) link new information (4) provide comprehensible input (5) modify vocabulary (6) use cooperative learning strategies and (7) modify testing. The reasons why those strategies were used by the teacher in teaching writing descriptive text are: (1) the strategies ease the students to understand the lesson (2) the strategies help the teacher to overcome boring class (3) the strategies help students to be more active. Keywords: Teacher’s Strategies, Writing, Descriptive Text